PENGEMBANGAN MODUL TERINTEGRASI AUGMENTED REALITY PADA PEMBELAJARAN MATERI SISTEM RANGKA MANUSIA SMA KELAS XI - Novita, Via Anggun; Oka, Anak Agung; Agus Sujarwanta (Prodi Pendidikan Biologi FKIP Universitas Muhammadiyah Metro, 2025)
This research aims to produce a product in the form of an integrated Augmented Reality (AR) module that is valid based on design and material validity tests and can facilitate students and educators to learn the biology learning material on the human skeletal system. The method used in this research is research and development with a 4-D (Four D) model which consists of four main stages, namely Define, Design, Develop, and Disseminate. The results of the module assessment by material experts obtained a feasibility percentage of 100% with